Independent and Combined Effects of Sex and Biological Maturation on Motor Coordination and Performance in Prepubertal Children - Luz, Leonardo G. O. (2017)
Sex differences and maturation-associated variation in fitness and motor coordination were examined in children aged 8-9 years (n = 128, 67 girls). Assessments included stature and body mass, two-component body composition, percentage of predicted adult stature (as an index of biological maturation), and motor performance and coordination (Körperkoordinationstest für Kinder). Compared to girls, boys were less advanced in maturation status, possessed larger fat mass, demonstrated superior performances in six tests of fitness, and obtained one superior score on the Körperkoordinationstest für Kinder. After controlling for somatic maturation, sex differences persisted in the two multivariate domains: motor performance and motor coordination.